Targeting Tumor Microenvironment: Effects of Chinese Herbal Formulae on Macrophage-Mediated Lung Cancer in Mice. (28th May 2017) - Xu, Fei; Cui, Wenqiang; Zhao, Zhengxiao; Gong, Weiyi; Wei, Ying; Liu, Jiaqi; Li, Mihui; Li, Qiuping; Yan, Chen; Qiu, Jian; Liu, Baojun; Dong, Jingcheng
Abstract : Our previous studies have shown that Qing-Re-Huo-Xue (QRHX) formulae had significant anti-inflammatory effects in chronic airway diseases such as asthma and chronic obstructive lung disease. Here, we examined the effects of QRHX on lung cancer cell invasion and the potential associated mechanism(s), mainly polarization of macrophages in the tumor microenvironment. In vivo, QRHX both inhibited tumor growth and decreased the number of tumor-associated macrophages (TAMs) in mice with lung cancer. Further study indicated that QRHX inhibited cancer-related inflammation in tumor by decreasing infiltration of TAMs and IL-6 and TNF- α production and meanwhile decreased arginase 1 (Arg-1) expression and increased inducible NO synthase (iNOS) expression. QRHX could markedly inhibit CD31 and VEGF protein expression. Additionally, CXCL12/CXCR4 expression and JAK2/STAT3 phosphorylation were reduced in QRHX treatment group. Thus, we draw that QRHX played a more important role in inhibiting tumor growth by regulating TAMs in mice, which was found to be associated with the inhibition of inflammation and the CXCL12/CXCR4/JAK2/STAT3 signaling pathway.